2003
DOI: 10.1364/ol.28.002067
|View full text |Cite
|
Sign up to set email alerts
|

Improved signal-to-noise ratio in spectral-domain compared with time-domain optical coherence tomography

Abstract: A signal-to-noise ratio (SNR) analysis is presented for optical coherence tomography (OCT) signals in which time-domain performance is compared with that of the spectral domain. A significant SNR gain of several hundredfold is found for acquisition in the spectral domain. The SNR benefit is demonstrated experimentally in a hybrid time-domain-spectral-domain OCT system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
665
0
10

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,197 publications
(679 citation statements)
references
References 12 publications
4
665
0
10
Order By: Relevance
“…The instrument is a high-speed UHR OCT system using spectral/Fourier domain detection. [34][35][36] Spectral/Fourier domain detection operates by first measuring the interference spectrum between backscattered or backreflected light from the tissue and light from a stationary reference arm. The magnitude and echo time delay of the light signal from the tissue is measured by taking the Fourier transform of this interference spectrum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument is a high-speed UHR OCT system using spectral/Fourier domain detection. [34][35][36] Spectral/Fourier domain detection operates by first measuring the interference spectrum between backscattered or backreflected light from the tissue and light from a stationary reference arm. The magnitude and echo time delay of the light signal from the tissue is measured by taking the Fourier transform of this interference spectrum.…”
Section: Methodsmentioning
confidence: 99%
“…Broad-bandwidth superluminescent diode light sources, similar to the one used in this study, recently have been shown to enable UHR OCT image resolution performance approaching that of femtosecond lasers. [27][28][29][30][31][32][33][34][35][36][37][38] Our research prototype high-speed UHR OCT system has been described in detail in previous publications. [29][30][31][32][33] This system can acquire up to 25 000 axial scans per second, corresponding to ~49 images (512 axial scans per image) per second.…”
Section: Methodsmentioning
confidence: 99%
“…1 Currently, the system in most widespread use is the third-generation time-domain (TD) StratusOCT (Carl Zeiss Meditec, Inc., Dublin, California), which has an axial resolution of 10 μm. 2 Recently, the development of Fourier-domain OCT (FD-OCT) provides an imaging speed that is ∼60 times faster and a resolution that is up to five times higher compared to TD-OCT. [3][4][5][6] Many instruments from different manufacturers are now commercially available that incorporate FD-OCT technology, one of them being RTVue-100 FD-OCT (Optovue Inc., Fremont, California), which has an axial resolution of 5 μm. 2 This device is able to measure total retinal thickness (RT) along with the thickness of the ganglion cell complex (GCC) in the macular area, the latter comprising the retinal nerve fiber layer, ganglion cell layer, and inner plexiform layer.…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering work in setting the stage for comparison between time domain OCT setups was reported by Rollins and Izatt [5] and Podoleanu [6]. As the interest in Fourier domain and swept source OCT has grown several groups independently proposed method to compare and translate the signal-to-noise results between time domain and Fourier domain systems [18][19][20].In this report we present an SNR analysis of our quadrature interferometric platform as integrated into a time domain system [5] followed by the correction proposed by Choma et al [20] to translate the SNR results for a SS-OCT.…”
Section: Signal To Noise Ratio Analysismentioning
confidence: 99%